Gambaran Kadar Asam Urat Pada Pasien Gagal Ginjal - Supriyatin Supriyatin; Misika Alam; Oktafirani Al Sas; Evita Nurjanah (Universitas Muhamadiyah Manado, 2021)
Uric acid or urine acid is a product of purine nucleic acid catabolism. Uric acid is produced from within the body (genetic) and from outside (food consumed). Uric acid is measured to assess purine metabolism abnormalities, to confirm the diagnosis and monitoring of treatment, and to detect abnormalities in kidney function. In this situation, the results of purine metabolism (uric acid) that should be excreted out of the body through the kidneys do not occur, so that uric acid in the blood will increase over time. Kidney failure disease kidney organ function has decreased so that eventually unable to work as a filter, dispose of body electrolytes, and maintain fluid and chemical balance in the blood or urine production. This study aims to determine uric acid levels and the percentage of uric acid levels that are outside the normal range and the relationship between hemodialysis time and uric acid levels in patients with kidney failure. The research method used is the descriptive method and the examination method uses the uricase enzymatic method. For data analysis using the SPSS Bivariate test program with Spearmen's Rank test with a sig value of 0.608 which was carried out on 32 samples of serum from hemodialysis patients at random. The results of this study showed that the average uric acid level was 7.1 mg/dL, while normal uric acid levels were 2.7 mg/dL, and the highest was 10.2 mg/dL. Uric acid levels that showed normal results were 12 respondents or 37.5% and increased results were 20 respondents or 62.5%. There is no relationship between the length of hemodialysis time and uric acid levels in patients with kidney failure.